Multi-vessel coronary artery grafting: analyzing the minimally invasive approach and its safety - Ushioda, Ryohei; Hirofuji, Aina; Yoongtong, Dit; Sakboon, Boonsap; Cheewinmethasiri, Jaroen; Lokeskrawee, Thanin; Patumanond, Jayanton; Lawanaskol, Suppachai; Kamiya, Hiroyuki; Arayawudhikul, Nuttapon (Frontiers in Cardiovascular Medicine, 2024)
At our institution, we perform off-pump coronary artery bypass (OPCAB) as a standard procedure. Moreover, patients with favorable coronary anatomy and condition are selected for minimally invasive cardiac surgery (MICS)-OPCAB. We retrospectively compared early outcomes, focusing on safety, between MICS-OPCAB and conventional off-pump techniques for multivessel coronary artery bypass grafting (CABG).From August 2017 to September 2022, 1,220 patients underwent multivessel coronary artery grafting at our institution. They were divided into the MICS-OPCAB group (MICS group = 163 patients) and the conventional OPCAB group (MS group = 1057 patients). Propensity score matching (1:1 ratio) was applied to the MICS-OPCAB and MS groups (149 patients per group) based on 23 preoperative clinical characteristics.After matching, there were no significant differences in preoperative characteristics between the groups. The MICS group had a lower total graft number (2.3 ± 0.6 versus 2.9 ± 0.8, p < 0.001) and fewer distal anastomoses (2.7 ± 0.8 versus 3.2 ± 0.9, p < 0.001). There were no significant differences in hospital stay, intensive care unit stay, postoperative complications, and 30-day mortality. The MICS group had less drain output , MS 450 ml ; p = 0.013). Kaplan-Meier analysis revealed no significant differences in postoperative MACCE (major adverse cardiac or cerebrovascular events)-free and survival rates between the groups (MACCE-free rate p = 0.945, survival rate p = 0.374).With proper patient selection, MICS-OPCAB can provide good short to mid-term results, similar to those of conventional OPCAB.